2005
DOI: 10.1021/ie050108t
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation Separation of Water/2-Propanol Mixtures by Use of the Blend Membranes of Sodium Alginate and (Hydroxyethyl)cellulose:  Roles of Permeate−Membrane Interactions, Zeolite Filling, and Membrane Swelling

Abstract: In an effort to improve membrane performance of pristine sodium alginate (NaAlg) for 2-propanol dehydration, blend membranes of NaAlg with (hydroxyethyl)cellulose (HEC) (5, 10, and 20 mass %) were prepared. Membranes were prepared by solution casting and cross-linked by a twostage process as confirmed by Fourier transform infrared spectroscopy. The blend membrane of NaAlg with 10 mass % HEC gave the highest selectivity of 63 000 for 5 mass % water in feed mixture (highest selectivity achieved so far in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…It is observed that PIC membranes offered superior performance compared to other polymeric membranes 20,41 -48 and hence these could be effective in dehydrating isopropanol from the aqueous streams; zeolite membranes offered better results due to molecular sieving action. 47,48 Evaluation of the performance of the PIC membrane incorporated with zeolite forms the future course of our work. …”
Section: Pervaporation Studies Effect Of Pei Content On Dehydration Omentioning
confidence: 99%
“…It is observed that PIC membranes offered superior performance compared to other polymeric membranes 20,41 -48 and hence these could be effective in dehydrating isopropanol from the aqueous streams; zeolite membranes offered better results due to molecular sieving action. 47,48 Evaluation of the performance of the PIC membrane incorporated with zeolite forms the future course of our work. …”
Section: Pervaporation Studies Effect Of Pei Content On Dehydration Omentioning
confidence: 99%
“…Further, it also improves mechanical properties of the membranes. Among the various adsorbents zeolite, 7,10,25 metal oxides, 4 sodium montmorillonite (Na-MMT), 24,26,27 etc., have been tried for making MMM. Incorporation of nanosize fillers as adsorbent in dense membrane improves its performance (normalized flux and selectivity) in both gas separation and pervaporation for several types of feed mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Double-distilled water was used throughout the experiments. Cellulose whiskers extracted from cotton linters were prepared by acid hydrolysis 8 performed using 64-65% (w/w) sulfuric acid (10 mL/g of cellulose) at 45 o C for about 60 min by arresting the reaction after diluting with cold water. The suspension was washed by centrifugation at 4900 rpm for 15 min at 25 o C, which was dialyzed using a dialysis pouch.…”
Section: Methodsmentioning
confidence: 99%